The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1080/10473289.2000.10464167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Fine Fraction of Particulate Matter versus the Coarse Mass and Other Pollutants on Daily Mortality in Santiago, Chile

Abstract: Daily counts of non-accidental deaths in Santiago, Chile, from 1988 to 1996 were regressed on six air pollutantsfine particles (PM 2.5 ), coarse particles (PM 10-2.5 ), CO, SO 2 , NO 2 , and O 3 . Controlling for seasonal and meteorological conditions was done using three different modelsa generalized linear model, a generalized additive model, and a generalized additive model on previously filtered data. Single-and two-pollutant models were tested for lags of 1-5 days and the average of the previous 2-5 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1
13

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(117 citation statements)
references
References 38 publications
1
98
1
13
Order By: Relevance
“…Epidemiological and toxicological studies conducted on particles with an aerodynamic diameter of 2.5 mm or less (PM 2.5 ), although limited in number, indicate that PM 2.5 has substantially greater toxicity than larger particles (Schwartz et al, 1996;Burnett et al, 2000;Cifuentes et al, 2000). One reason for the lack of studies investigating the health effects of PM 2.5 may be that it was not consistently monitored by the Environmental Protection Agency (EPA) until 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and toxicological studies conducted on particles with an aerodynamic diameter of 2.5 mm or less (PM 2.5 ), although limited in number, indicate that PM 2.5 has substantially greater toxicity than larger particles (Schwartz et al, 1996;Burnett et al, 2000;Cifuentes et al, 2000). One reason for the lack of studies investigating the health effects of PM 2.5 may be that it was not consistently monitored by the Environmental Protection Agency (EPA) until 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Prior analyses indicate that particulate matter less than 10 mm in aerodynamic diameter (PM 10 ) may be associated with preterm birth in southern California (Ritz et al, 2000); in the Czech Republic, exposure to high levels of PM 10 and particulate matter with less than 2.5 mm in aerodynamic diameter (PM 2.5 ) were found to reduce intrauterine growth (Dejmek et al, 1999). PM 2.5 appears to be the more potent portion of the particulate matter mixture, resulting in different adverse health risks than those from exposure to PM 10 or coarse particles (PM 10 -PM 2.5 ) (Cifuentes et al, 2000;Schwartz and Neas, 2000). Furthermore, PM 2.5 offers a measure for pollutant exposure with relatively high correlations between ambient and indoor concentrations (U.S. EPA, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggest that it is the finer particles, which have the greatest impact on health (Schwartz et al 1996;Cifuentes et al 2000), which is supported by the fact that PM 2.5 penetrates the human respiratory system more efficiently into the alveolar region. Nevertheless, studies have also found that higher concentrations of coarse particles (PM 2.5-10 ) can also increase overall mortality rates (Castillejos et al 2000).…”
Section: Effects Of Particulate Mattermentioning
confidence: 58%